Measurement of hematological and biochemical parameters in sheep infected with intestinal protozoa and helminthes - Shaimaa Jamal Aziz; Omaima Ibrahim Mahmoud (Tikrit Journal of Pure Science)
Fifty blood samples were collected from sheep of different regions in Salah Al-Din Governorate for the period from November 2019 to April 2020 to detected some hematological and biochemical criteria and the infection with intestinal protozoa (Eimeria, Cryptosporidium) and helminthes (Marshallagia sp, Trichostrongylus sp, Ostertagia sp ,Haemonchus sp, Chabertia sp , Nematodirus sp , Toxocara sp, Cooperia sp , Oesophagostomum sp , Strongyloid sp) .